Islamic state: the digital caliphate - Atwan, Abdel Bari (Saqi Books, 2015)
"Islamic State stunned the world when it overran an area the size of Britain on both sides of the Iraq-Syria border in a matter of weeks and proclaimed the birth of a new Caliphate. In this timely and important book, Abdel Bari Atwan draws on his unrivaled knowledge of the global jihadi movement and Middle Eastern geopolitics to reveal the origins and modus operandi of Islamic State. Based on extensive field research and exclusive interviews with IS insiders, Atwan outlines the group's leadership structure, as well as its strategies, tactics and diverse methods of recruitment. He traces the Salafi-jihadi lineage of IS, its ideological differences with al-Qa'ida and the deadly rivalry that has emerged between their leaders. Atwan also shows how the group's rapid growth has been facilitated by its masterful command of social media platforms, the 'dark web', Hollywood 'blockbuster'-style videos, and even jihadi computer games, producing a powerful paradox where the ambitions of the Middle Ages have re-emerged in cyber-space. As Islamic State continues to dominate the world's media headlines with horrific acts of ruthless violence, Atwan considers the movement's chances of survival and expansion, and offers indispensable insights on potential government responses to contain the IS threat"--Provided by publisher